DNA damage modeled with Geant4-DNA: effects of plasmid DNA conformation and experimental conditions - D-Kondo, N; Moreno-Barbosa, E; Štěphán, V; Stefanová, K; Perrot, Y; Villagrasa, C; Incerti, S; De Celis Alonso, B; Schuemann, J; Faddegon, B; Ramos-Méndez, J (Physics in medicine and biology, 2021)
The chemical stage of the Monte Carlo track-structure (MCTS) code Geant4-DNA was extended for its use in DNA strand break (SB) simulations and compared against published experimental data. Geant4-DNA simulations were performed using pUC19 plasmids (2686 base pairs) in a buffered solution of DMSO irradiated by60Co or137Csγ-rays. A comprehensive evaluation of SSB yields was performed considering DMSO, DNA concentration, dose and plasmid supercoiling. The latter was measured using the super helix density value used in a Brownian dynamics plasmid generation algorithm. The Geant4-DNA implementation of the independent reaction times method (IRT), developed to simulate the reaction kinetics of radiochemical species, allowed to score the fraction of supercoiled, relaxed and linearized plasmid fractions as a function of the absorbed dose. The percentage of the number of SB after •OH + DNA and H• + DNA reactions, referred as SSB efficiency, obtained using MCTS were 13.77% and 0.74% respectively. This is in reasonable agreement with published values of 12% and 0.8%. The SSB yields as a function of DMSO concentration, DNA concentration and super helix density recreated the expected published experimental behaviors within 5%, one standard deviation. The dose response of SSB and DSB yields agreed with published measurements within 5%, one standard deviation. We demonstrated that the developed extension of IRT in Geant4-DNA, facilitated the reproduction of experimental conditions. Furthermore, its calculations were strongly in agreement with experimental data. These two facts will facilitate the use of this extension in future radiobiological applications, aiding the study of DNA damage mechanisms with a high level of detail.
Keywords: konformace nukleové kyseliny; DNA Damage; metoda Monte Carlo; Nucleic Acid Conformation; geant4-DNA; Computer Simulation; DNA; počítačová simulace; poškození DNA; plasmid; simulation; radiation chemistry; DNA damage; dimethylsulfoxid; Plasmids; plazmidy; track-structure; Monte Carlo Method; Dimethyl Sulfoxide